2020
DOI: 10.3390/su12187749
|View full text |Cite
|
Sign up to set email alerts
|

Food Values, Benefits and Their Influence on Attitudes and Purchase Intention: Evidence Obtained at Fast-Food Hamburger Restaurants

Abstract: This paper analyzes the effects of: (i) Food values on their related benefits (hedonic and utilitarian); (ii) both kinds of benefits on attitudes toward eating hamburgers; and (iii) attitudes on purchase intention. To this end, we adapted the food values scale to the context of fast-food hamburger restaurants. Data were collected from a survey of 512 Mexican consumers and analyzed using structural equation modeling (SEM). The results show that the strongest influences are those exerted by food values, first, o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 67 publications
3
13
0
Order By: Relevance
“…Unbranded product imagery appeared in the top three marketing strategies for all the investigated OFD platforms. The 'sight' or appearance of food has been suggested to be a high food value with impacts on purchase intention (51) and can result in higher levels of consumption of the food/product (52) . Taken together, the imagery of foods is a powerful tool to market poor nutritional quality food and has significant impacts on consumer behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…Unbranded product imagery appeared in the top three marketing strategies for all the investigated OFD platforms. The 'sight' or appearance of food has been suggested to be a high food value with impacts on purchase intention (51) and can result in higher levels of consumption of the food/product (52) . Taken together, the imagery of foods is a powerful tool to market poor nutritional quality food and has significant impacts on consumer behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, we followed several studies and emphasized purchase intention as an important factor [9][10][11]. The literature review confirmed that several Sustainability 2021, 13, 12857 2 of 16 variables from the Theory of Planned Behavior (hereafter TPB) influence food purchase intention [12][13][14][15][16][17]. According to Ellison et al (2021) [18], there is an ongoing shift toward online food purchasing, while Choi et al (2021) [10] affirmed that more people are using food delivery apps.…”
Section: Introductionmentioning
confidence: 99%
“…In the north of America, another study [27] revealed that Canadian consumers emphasized taste, safety, nutrition, and price as the most preferred food values in relation to nanotechnology foods. In Mexico, other scholars focused on the behavioral attitudes of fast food consumers [28,29] and found that food values and positive anticipated emotions impacted people's attitudes toward the brand, which then impacted consumers' purchase intentions. In their studies, it was revealed that the positive anticipated emotions exerted a greater impact than food values, thus suggesting that the best method of boosting purchase intention is by improving attitude toward the brand rather than attitude toward eating a hamburger [28,29].…”
Section: Main Results Of the Papersmentioning
confidence: 99%
“…In Mexico, other scholars focused on the behavioral attitudes of fast food consumers [28,29] and found that food values and positive anticipated emotions impacted people's attitudes toward the brand, which then impacted consumers' purchase intentions. In their studies, it was revealed that the positive anticipated emotions exerted a greater impact than food values, thus suggesting that the best method of boosting purchase intention is by improving attitude toward the brand rather than attitude toward eating a hamburger [28,29]. In general, it was observed that fast food consumers assigned more importance to the hedonic than to the utilitarian benefits of food [28,29].…”
Section: Main Results Of the Papersmentioning
confidence: 99%
See 1 more Smart Citation